Circadian Rhythm Influences the Promoting Role of Pulsed Electromagnetic Fields on Sciatic Nerve Regeneration in Rats - Zhu, Shu; Ge, Jun; Liu, Zhongyang; Liu, Liang; Jing, Da; Ran, Mingzi; Wang, Meng; Huang, Liangliang; Yang, Yafeng; Huang, Jinghui; Luo, Zhuojing (Frontiers in Neurology, 2017)
Circadian rhythm (CR) plays a critical role in the treatment of several diseases. However, the role of CR in the treatment of peripheral nerve defects has not been studied. It is also known that the pulsed electromagnetic fields (PEMF) can provide a beneficial microenvironment to fast the process of nerve regeneration and to enhance the quality of reconstruction. In this study, we evaluate the impact of CR on the promoting effect of PEMF on peripheral nerve regeneration in rats. We used the self-made “collagen-chitosan” nerve conduits to bridge the 15mm nerve gaps in Sprague–Dawley rats. Our results show that PEMF stimulation at daytime (DPEMF) has most effective outcome on nerve regeneration, and rats with DPEMF treatment achieve quickly functional recovery after 12 weeks. These findings indicate that CR is an important factor that determines the promoting effect of PEMF on peripheral nerve regeneration. PEMF exposure in the daytime enhances the functional recovery of rats. Our study provides a helpful guideline for the effective use of PEMF mediations experimentally and clinically.